The Effect of Community Concern on Interest in Saving at the Jaya Abadi Waste Bank, Jambi City - Erris; Bambang Ariyadi; V.A Irmayanti Harahap (Jurnal Ekonomi dan Bisnis Digital, 2023)
The garbage bank is a concept for gathering dry waste, sorting it, and managing it like a bank, but the material being stored is garbage rather than money. The Independent Mean Different Test (Independent T-Test) is a type of analysis used in research to look at differences between the two groups. Its purpose is to ascertain the level of public awareness of the interest in saving at the Jaya Abadi Waste Bank, located in Jambi City. It was discovered that what affects the occurrence of this interest is not only caused by one factor but will still be influenced by internal factors, i.e., something that piques people's interest and originates within a person. Internal factors are the focus of attention, curiosity, motivation, and needs”; external factors are something that makes interests come from outside oneself, such as family, co-workers, available facilities and infrastructure, or facilities and conditions.